Learning from entrepreneurial failure : emotions, cognitions, and actions - Shepherd, Dean A. (Cambridge : Cambridge University Press, 2016)
Learning from Entrepreneurial Failure provides an important counterweight to the multitude of books that focus on entrepreneurial success. Failure is by far the most common scenario for new ventures and a critical part of the entrepreneurial process is learning from failure and having the motivation to try again. This book examines the various obstacles to learning from failure and explores how they can be overcome. A range of topics are discussed that include why some people have a more negative emotional reaction to failure than others and how these negative emotions can be managed; why some people delay the decision to terminate a poorly performing entrepreneurial venture; anti-failure biases and stigmatism in organizations and society; and the role that the emotional content of narratives plays in the sense-making process. This thought-provoking book will appeal to academic researchers, graduate students and professionals in the fields of entrepreneurship and industrial psychology.
Title from publisher's bibliographic system (viewed on 08 Mar 2016).
Keywords: Entrepreneurship; Business failures